Peningkatan kesehatan gigi anak disabilitas melalui pelayanan asuhan kesehatan gigi berbasis Home Care di SLB Negeri Pembina Provinsi Aceh - Rahayu, Eka Sri; Reca, Reca (Jurnal PADE: Pengabdian & Edukasi, 2025)
Oral health issues remain a significant challenge for children with special needs, particularly at the Special Needs School for Special Needs (SLB) in Aceh Province, located in Gampong Lamreung, Aceh Besar Regency. Initial observations indicate that 70% of children suffer from dental caries, with an average Oral Hygiene Score (OHIS) of 2.8, well above the national standard of <1.2. This condition is exacerbated by children's limited ability to maintain dental hygiene independently. The decreased quality of life of children due to chewing difficulties, pain, and lack of sleep has become an urgent need for this community service initiative. This activity aims to improve the dental health of children with disabilities through home-based dental care. The method used is a descriptive quantitative approach with an educational approach for parents, particularly mothers, through counseling, demonstrations of toothbrushing techniques, and three home visits over 14 days. The evaluation was conducted using a questionnaire through pre-test, post-test I, and post-test II on 20 pairs of mothers and children. The intervention results showed an improvement in maternal behavior, from 65% in the adequate category (pre-test) to 90% in the good category (post-test II). The children's dental hygiene status also improved significantly, from 100% in the poor category (pre-test) to 80% in the good category (post-test II). In conclusion, the home care approach has proven effective in improving maternal roles and improving the dental hygiene status of children with disabilities. It is recommended that similar programs be replicated in other special needs schools with ongoing involvement of schools and healthcare professionals.